Evaluation and modelling the effect of size, surface area and moisture content on breaking characteristics of African mango nut - Oduma, Okechukwu; Okeke, Glory C.; Orji, Francis N.; Ehiem, James Chinaka; Ugwu, Elijah C.; Igbozulike, Augustine Onyekachi; Aviara, Aviara Ndubisi (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: African mango nut is a valuable but underutilized forest product due to dearth of research. This study was conducted to evaluate and model the effect of size, surface area, and moisture content on breaking characteristics of African mango nut, for appropriate selection and development of the nut cracking machine to minimize seed damage, curb energy wastage, and improve the processing operation. Method: This study was carried out at African mango nut moisture content range of 15–20% wet basis using standard methodologies from literature. Findings: Results showed that breaking of African mango nut requires compressive strength ranging from 411.23–414.18 N/cm2 for nut of sizes between 3.24–3.49 cm and surface areas varying from 8.66–11.11 cm2. The values of the yield strength recorded during the force-deformation (compression) process followed the same trend. Also, the compressive strength was found to increase with increase in moisture content and the consequential effect of increasing the moisture content as from 15 to 20 % on compressive force is higher than the resultant impact noticed in increasing the size between 3.24 and 3.49 cm and the surface area between 8.66 and 11.11 cm2. The linear models developed were statistically significant at P < 0.05 with coefficient of determination (R2) of 0.9902 and 0.9730 for compressive and yield strengths, respectively. Conclusions: The findings contribute to sustainable nut processing practices and energy-efficient food production in tropical regions. It also shows that a good relationship exists between the dependent and independent variables studied. Novelty/Originality of this article: Farmers and processors of African mango seeds could, select, design and create, or assess the cracking/breaking contrivance with the developed model equations.